DESAIN DIDAKTIS UNTUK MENGATASI HAMBATAN BELAJAR SISWA SD PADA PEMAHAMAN KONSEP LUAS BANGUN DATAR - Rizki Siti Hasnani; Riana Irawati; Maulana Maulana (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This research focused on students who faced challenges in understanding concepts of two-dimensional area. The primary cause of these learning obstacles was the lack of mastery and comprehension in mathematics. To address this, a didactical design was developed based on the principles of the Realistic Mathematics Education (RME) model, aimed at helping students overcome these difficulties. This design was initially tested with fourth-grade students to observe their responses during the learning process. Despite some unforeseen reactions, the analysis of these initial implementations informed a revised design, which was subsequently tested again. The didactical design was divided into three sessions, each with anticipated student responses in mind. The research employed Didactical Design Research (DDR) using qualitative methods, including learning barrier tests, short fill-in lists, interviews, questionnaires, documentation, and field notes for data collection. The study resulted in a didactical design that could be effectively used to improve students' understanding of two-dimensional area concepts in mathematics.